2022
DOI: 10.1103/physrevfluids.7.094003
|View full text |Cite
|
Sign up to set email alerts
|

Effect of ambient gas on cavity formation for sphere impacts on liquids

Abstract: How to cite:Please refer to published version for the most recent bibliographic citation information. If a published version is known of, the repository item page linked to above, will contain details on accessing it.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 36 publications
1
3
0
Order By: Relevance
“…These results are in line with research on water entry of a sphere at reduced ambient pressures (Gilbarg & Anderson 1948;Abelson 1970;Yakimov 1973). Furthermore, in the recent work of Williams et al (2022), it was found that the most important gas parameter influencing the lamella ejection is the gas density. Although, in the latter, air density prevents cavity collapse by resisting the contact line movement (Williams et al 2022).…”
Section: Bernoulli Suction Regimesupporting
confidence: 87%
See 2 more Smart Citations
“…These results are in line with research on water entry of a sphere at reduced ambient pressures (Gilbarg & Anderson 1948;Abelson 1970;Yakimov 1973). Furthermore, in the recent work of Williams et al (2022), it was found that the most important gas parameter influencing the lamella ejection is the gas density. Although, in the latter, air density prevents cavity collapse by resisting the contact line movement (Williams et al 2022).…”
Section: Bernoulli Suction Regimesupporting
confidence: 87%
“…Although, in the latter, air density prevents cavity collapse by resisting the contact line movement (Williams et al. 2022).…”
Section: Cavity Dynamics Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…The interplay of dynamic wetting and gas films also underpins the relation between precontact and postcontact dynamics, explored by Zhang et al (2022) and by de Goede et al ( 2019) under different ambient conditions; the entrapment of gas bubbles during spreading (Thoroddsen et al 2010); the remarkable extreme wetting of liquid bridges that have formed in drop contact spots (Langley et al 2017); the influence of gas on cavity formation when solid spheres impact baths (see Figure 9b) (Duez et al 2007, Williams et al 2022; and the stability of wetting contacts on hot surfaces, which govern Leidenfrost stability (Chantelot & Lohse 2021b).…”
Section: Dynamic Wettingmentioning
confidence: 89%